Carbamate-Protected (BOC and O-NB) 2-Aminopyrimidinedione-based janus G-C nucleobase motifs as building blocks for supramolecular assembly and smart polymers - Singh, Dharmendra; Lakshmi, Durga; Meena, Chhuttan L.; Krishna, Gamidi Rama; Sanjayan, Gangadhar J. (Journal of organic chemistry, 2023)
In this paper, we report ``carbamate protected'' 2-aminopyrimidinedione-based Janus G-C nucleobases (2-APD Janus G-C nucleobases) featuring polymerizable groups and self-complementary triple H-bonding motifs DDA and AAD as building blocks for developing smart polymers and self-healing materials. The carbamate-masked H-bonding motif, cleavable under acidic (BOC group) or photocleavable (O-nitrobenzyl group) conditions, would facilitate the synthesis of smart polymers by alleviating aggregation during polymerization which in turn would exclude self-assembly-assisted solubility issues. Ready accessibility in excellent yields coupled with the possibility for facile introduction of polymerizable groups would make these building blocks excellent candidates for diverse polymerization applications.

Design, synthesis, and adhesive performance evaluation of DOPA-Functionalized polyurethane elastomers - Davis, Disiya; Alam, Md Shafi; Purushothaman Bindu, Bhadra; Lakshmi, Durga; N Muhammed, Hasin; Torris, Arun; Ambade, Ashootosh V.; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Functional polyurethane (PU) hot-melt adhesives were developed through the incorporation of a dopamine-derived chain extender (DADO) into thermoplastic PUs. The DADO monomer was synthesized via a four-step route and successfully integrated into the PU backbone using a one-pot, two-step polymerization involving polycaprolactone-diol and 4,4 `-methylenebis(phenyl isocyanate). Spectral analyses confirmed the formation of urethane linkages and the effective incorporation of catechol moieties. Monomodal molecular weight distributions were obtained through size-exclusion chromatography with Mn ranging from 12,000 to 17,000 g/mol. Thermal analyses demonstrated two-step decomposition behavior and a progressive increase in glass transition temperature with increasing DADO content. Mechanical testing revealed that there was substantial improvement in the tensile strength of these materials from 1.34 MPa for unmodified PU (PU-0) to 14.3 MPa for PU-10. Adhesion performance exhibited a similar trend, with PU-10 attaining the highest lap-shear strength of 3.92 +/- 0.19 MPa on the Al substrate. PU-10 exhibited the highest lap-shear strength of 3.92 +/- 0.19 MPa on aluminum and superior underwater stability with a value of 2.78 +/- 0.47 MPa compared to other formulations. Overall, controlled incorporation of DADO significantly enhances properties, and PU-10 represents the optimal formulation for high-performance hot-melt PU adhesives.
Keywords: chain extender; dopamine; hot-melt adhesive; polycaprolactone diol; polyurethanes

Dynamic janus hydrogen bond mimicry unlocks tough, flexible supramolecular elastomers for strain sensing - Lakshmi, Durga; Wagh, Mahendra A.; Sharma, Aakash; Alam, Md Shafi; Selvan, T. Muthamil; Torris, Arun; Mondal, Titash; Sanjayan, Gangadhar J.; Nair, Kiran Sukumaran (Chemistry of Materials, 2026)
Flexible and wearable electronics demand stretchable sensors with polymer elastomers as key matrixes for mechanical flexibility and durability. However, despite their excellent elasticity, their limited mechanical strength remains a challenge. To address this limitation, in this study, we report the rational design of supramolecular polyurethane elastomers (SPUs) incorporating nucleobase-inspired aminopyrimidinedione with DDA-AAD (G-C mimic) reversible triple hydrogen bonds. This dual-domain architecture gives rise to a durable supramolecular network with enhanced mechanical properties, yielding elastomers that are soft, stretchable, and tough. By tuning of the density of dynamic cross-links, mechanical properties were systematically modulated. SPU-0.5 exhibited a maximum tensile strength of 16.14 MPa, representing a 67-fold strength enhancement over that of SPU-0. Although increasing the aminopyrimidinedione (APD) content reduced elongation, SPU-0.2 retained a high elongation of 1060% and showed the lowest residual strain during cyclic tests. To be of great interest, the activation energy increased with increasing hydrogen bonding content up to SPU-0.1, whereas beyond SPU-0.2 it decreased, likely due to extensive hydrogen bond formation. Furthermore, SPU-0.2-SP, a conductive variant, demonstrated a promising strain-sensing performance even after hundreds of cycles. Overall, the insights gained from this study advance the development of intelligent soft materials and lay the groundwork for next-generation flexible and wearable electronic devices.